Synthesis of imidazo[1,5-a]pyridines via cyclocondensation of 2-(aminomethyl)pyridines with electrophilically activated nitroalkanes - Aksenov, Dmitrii A.; Arutiunov, Nikolai A.; Maliuga, Vladimir V.; Aksenov, Alexander V.; Rubin, Michael (Beilstein Journal of Organic Chemistry, 2020)
Imidazo[1,5-a]pyridines were efficiently prepared via the cyclization of 2-picolylamines with nitroalkanes electrophilically activated in the presence of phosphorous acid in polyphosphoric acid (PPA) medium.
Keywords: cyclization; heterocycles; imidazo[1,5-a]pyridines; nitroalkanes; polyphosphoric acid

(untitled) - Calcul, L.; Longeon, A.; Al Mourabit, A.; Guyot, M.; Bourguet-Kondracki, M.-L. (Tetrahedron, 2003)

(untitled) - Pettit, G. R.; Collins, J. C.; Knight, J. C.; Herald, D. L.; Nieman, R. A.; Williams, M. D.; Pettit, R. K. (J. Nat. Prod., 2003)

(untitled) - Yu, H.-B.; Yang, F.; Sun, F.; Ma, G.-Y.; Gan, J.-H.; Hu, W.-Z.; Han, B.-N.; Jiao, W.-H.; Lin, H.-W. (J. Nat. Prod., 2014)

(untitled) - Augustin, E.; Pawłowska, M.; Polewska, J.; Potega, A.; Mazerska, Z. (Cell Biol. Int., 2013)

(untitled) - Isambert, N.; Campone, M.; Bourbouloux, E.; Drouin, M.; Major, A.; Yin, W.; Loadman, P.; Capizzi, R.; Grieshaber, C.; Fumoleau, P. (Eur. J. Cancer, 2010)

(untitled) - Paradziej-Łukowicz, J.; Skwarska, A.; Peszyńska-Sularz, G.; Brillowska-Dąbrowska, A.; Konopa, J. (Cancer Biol. Ther., 2011)

(untitled) - Polewska, J.; Skwarska, A.; Augustin, E.; Konopa, J. (J. Pharmacol. Exp. Ther., 2013)

(untitled) - Skwarska, A.; Augustin, E.; Konopa, J. (Apoptosis, 2007)

(untitled) - Zaffaroni, N.; De Marco, C.; Villa, R.; Riboldi, S.; Daidone, M. G.; Double, J. A. (Eur. J. Cancer, 2001)

(untitled) - Gresele, P.; Blockmans, D.; Deckmyn, H.; Vermylen, J. (J. Pharmacol. Exp. Ther., 1988)

(untitled) - Huang, A.; Sun, D.; Koller, A. (Hypertension, 1993)

(untitled) - Reilly, I. A.; Doran, J. B.; Smith, B.; FitzGerald, G. A. (Circulation, 1986)

(untitled) - Volpi, G.; Garino, C.; Priola, E.; Magistris, C.; Chierotti, M. R.; Barolo, C. (Dyes Pigm., 2019)

(untitled) - Cui, Y.; Ge, Y.; Li, Y.; Tao, J.; Yao, J.; Dong, Y. (Struct. Chem., 2020)

(untitled) - Park, D.-A.; Byun, S.; Ryu, J. Y.; Lee, J.; Lee, J.; Hong, S. (ACS Catal., 2020)

(untitled) - Volpi, G.; Lace, B.; Garino, C.; Priola, E.; Artuso, E.; Cerreia Vioglio, P.; Barolo, C.; Fin, A.; Genre, A.; Prandi, C. (Dyes Pigm., 2018)

(untitled) - Volpi, G.; Garino, C.; Priola, E.; Diana, E.; Gobetto, R.; Buscaino, R.; Viscardi, G.; Barolo, C. (Dyes Pigm., 2017)

(untitled) - Singh, D.; Kumar, V.; Devi, N.; Malakar, C. C.; Shankar, R.; Singh, V. (Adv. Synth. Catal., 2017)

(untitled) - Buil, M. A.; Calbet, M.; Castillo, M.; Castro, J.; Esteve, C.; Ferrer, M.; Forns, P.; González, J.; López, S.; Roberts, R. S.; Sevilla, S.; Vidal, B.; et al. (Eur. J. Med. Chem., 2016)

(untitled) - Chino, A.; Masuda, N.; Amano, Y.; Honbou, K.; Mihara, T.; Yamazaki, M.; Tomishima, M. (Bioorg. Med. Chem., 2014)

(untitled) - Amini-Rentsch, L.; Vanoli, E.; Richard-Bildstein, S.; Marti, R.; Vilé, G. (Ind. Eng. Chem. Res., 2019)

(untitled) - Bosch, P.; García, V.; Bilen, B. S.; Sucunza, D.; Domingo, A.; Mendicuti, F.; Vaquero, J. J. (Dyes Pigm., 2017)

(untitled) - Tverdiy, D. O.; Chekanov, M. O.; Savitskiy, P. V.; Syniugin, A. R.; Yarmoliuk, S. M.; Fokin, A. A. (Synthesis, 2016)

(untitled) - Kurhade, S.; Konstantinidou, M.; Sutanto, F.; Kurpiewska, K.; Kalinowska-Tłuścik, J.; Dömling, A. (Eur. J. Org. Chem., 2019)

(untitled) - Nirogi, R.; Mohammed, A. R.; Shinde, A. K.; Bogaraju, N.; Gagginapalli, S. R.; Ravella, S. R.; Kota, L.; Bhyrapuneni, G.; Muddana, N. R.; Benade, V.; Palacharla, R. C.; Jayarajan, P.; et al. (Eur. J. Med. Chem., 2015)

(untitled) - Roberts, L. R.; Bradley, P. A.; Bunnage, M. E.; England, K. S.; Fairman, D.; Fobian, Y. M.; Fox, D. N. A.; Gymer, G. E.; Heasley, S. E.; Molette, J.; Smith, G. L.; Schmidt, M. A.; et al. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Trotter, B. W.; Nanda, K. K.; Burgey, C. S.; Potteiger, C. M.; Deng, J. Z.; Green, A. I.; Hartnett, J. C.; Kett, N. R.; Wu, Z.; Henze, D. A.; Della Penna, K.; Desai, R.; et al. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Kurhade, S.; Diekstra, E.; Sutanto, F.; Kurpiewska, K.; Kalinowska-Tłuścik, J.; Dömling, A. (Org. Lett., 2018)

(untitled) - Fuse, S.; Ohuchi, T.; Asawa, Y.; Sato, S.; Nakamura, H. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Murai, T.; Nagaya, E.; Shibahara, F.; Maruyama, T. (Org. Biomol. Chem., 2012)

(untitled) - Tahara, S.; Shibahara, F.; Maruyama, T.; Murai, T. (Chem. Commun., 2009)

(untitled) - Ramesha, A. B.; Pavan Kumar, C. S.; Sandhya, N. C.; Kumara, M. N.; Mantelingu, K.; Rangappa, K. S. (RSC Adv., 2016)

(untitled) - Ramesha, A. B.; Sandhya, N. C.; Pavan Kumar, C. S.; Hiremath, M.; Mantelingu, K.; Rangappa, K. S. (New J. Chem., 2016)

(untitled) - Späth, A.; Gonschor, J.; König, B. (Monatsh. Chem., 2011)

(untitled) - Bori, J.; Behera, N.; Mahata, S.; Manivannan, V. (ChemistrySelect, 2017)

(untitled) - Li, M.; Xie, Y.; Ye, Y.; Zou, Y.; Jiang, H.; Zeng, W. (Org. Lett., 2014)

(untitled) - Shibahara, F.; Sugiura, R.; Yamaguchi, E.; Kitagawa, A.; Murai, T. (J. Org. Chem., 2009)

(untitled) - Aksenov, A. V.; Aksenov, N. A.; Nadein, O. N.; Aksenova, I. V. (Synlett, 2010)

(untitled) - Aksenov, A. V.; Aksenov, N. A.; Orazova, N. A.; Aksenov, D. A.; Dmitriev, M. V.; Rubin, M. (RSC Adv., 2015)

(untitled) - Aksenov, N. A.; Aksenov, A. V.; Nadein, O. N.; Aksenov, D. A.; Smirnov, A. N.; Rubin, M. (RSC Adv., 2015)

(untitled) - Aksenov, A. V.; Smirnov, A. N.; Aksenov, N. A.; Bijieva, A. S.; Aksenova, I. V.; Rubin, M. (Org. Biomol. Chem., 2015)

(untitled) - Aksenov, A. V.; Aksenov, N. A.; Ovcharov, D. S.; Aksenov, D. A.; Griaznov, G.; Voskressensky, L. G.; Rubin, M. (RSC Adv., 2016)

(untitled) - Aksenov, A. V.; Ovcharov, D. S.; Aksenov, N. A.; Aksenov, D. A.; Nadein, O. N.; Rubin, M. (RSC Adv., 2017)

(untitled) - Aksenov, A. V.; Aksenov, N. A.; Arutiunov, N. A.; Malyuga, V. V.; Ovcharov, S. N.; Rubin, M. (RSC Adv., 2019)

(untitled) - Aksenov, A. V.; Khamraev, V.; Aksenov, N. A.; Kirilov, N. K.; Domenyuk, D. A.; Zelensky, V. A.; Rubin, M. (RSC Adv., 2019)

(untitled) - Aksenov, N. A.; Arutiunov, N. A.; Kirillov, N. K.; Aksenov, D. A.; Aksenov, A. V.; Rubin, M. (Chem. Heterocycl. Compd., 2020)

(untitled) - Aksenov, N. A.; Aksenov, A. V.; Kirilov, N. K.; Arutiunov, N. A.; Aksenov, D. A.; Maslivetc, V.; Zhao, Z.; Du, L.; Rubin, M.; Kornienko, A. (Org. Biomol. Chem., 2020)

(untitled) - Klingele, M. H.; Moubaraki, B.; Murray, K. S.; Brooker, S. (Chem. – Eur. J., 2005)

(untitled) - Huhti, A.-L.; Gartaganis, P. A. (Can. J. Chem., 1956)

(untitled) - Uhlig, F. (Angew. Chem., 1954)

(untitled) - Lyapchev, R.; Petrov, P.; Dangalov, M.; Vassilev, N. G. (J. Organomet. Chem., 2017)

(untitled) - Zhao, Q.; Liu, S.; Li, Y.; Wang, Q. (J. Agric. Food Chem., 2009)

(untitled) - Vu, T. Y.; Chrostowska, A.; Huynh, T. K. X.; Khayar, S.; Dargelos, A.; Justyna, K.; Pasternak, B.; Leśniak, S.; Wentrup, C. (Chem. – Eur. J., 2013)

(untitled) - Winterfeld, K.; Franzke, H. (Angew. Chem., 1963)